Translanguaging Practices in English Language Teaching: (A Sociolinguistic Study of Language Choice and Classroom Interaction) - Fahria Musa’ad; Wahyu Andini; St. Mutiah Nurul Ilmidarajatih; Saiful; Nur Qalbi (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
English language teaching in multilingual contexts is deeply intertwined with language choice and learners' linguistic identities. This study examines translanguaging practices from a sociolinguistic perspective at SDI 100 Kepulauan Selayar, Indonesia, to address the gap in primary school EFL research. The study aims to investigate the patterns of English-Indonesian use, identify emerging forms of translanguaging, and analyze its sociolinguistic functions in classroom interaction. This research employed a qualitative descriptive design with data collected through non-participant observations, audio recordings, and semi-structured interviews. The findings indicate that English and Indonesian were used systematically; English served formal instruction, while Indonesian was used for clarification and affective support. Various forms of translanguaging, including teacher-initiated and peer interaction, functioned as instructional scaffolding that validated students' multilingual identities and reduced anxiety. This study concludes that translanguaging is an effective pedagogical practice that supports comprehension and engagement, suggesting that context-sensitive approaches are essential for multilingual primary education.